Criminal Liability of COD Couriers As Narcotics Intermediaries: an Analysis of Article 114 of The Narcotics Law And the New Criminal Code - Preden Ginting; Ujuh Juhana (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
The proliferation of digital commerce has enabled a new narcotics distribution mode through Cash on Delivery (COD) systems that exploit delivery couriers as intermediaries, systematically obscuring criminal trails and placing intellectual perpetrators beyond immediate risk of arrest. This study analyzes the regulation and application of criminal liability of COD couriers as narcotics intermediaries under Article 114(1) of Law No. 35 of 2009 on Narcotics, reviewed against the New Criminal Code (Law No. 1 of 2023), while critically examining the practice of proving the intent element in Bandung City. A normative-empirical legal method was employed, integrating statutory, conceptual, case-based, and comparative approaches. Empirical data were obtained from the Narcotics Criminal Investigation Unit of Polrestabes Bandung, which handled 92 cases involving 117 suspects across three monitoring periods in 2024. The research reveals that the phrase